Perancangan Sistem Informasi Absensi Siswa Berbasis Mobile pada SMK Pemda Lubuk Pakam - Alda, Muhamad; Utami, Yulia; Chairullah, Andry; Kumala, Winda; Husaini, Adam (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
The design of a mobile-based student attendance information system at SMK Pembangunan Daerah Lubuk Pakam is carried out as a step to improve efficiency and accuracy in managing student attendance data. The previous attendance process, which was still manual, often caused reporting delays and potential data recording errors. In its development, the Waterfall method is used, focusing on the stages of requirement analysis and system design using UML diagrams (Use Case, Activity, and Class Diagram). The result of this study is a system design that has been validated through functional scenario testing (Black Box Design). Logical testing results show that the attendance process flow using QR Code, automatic data recap, and database integration has run 100% according to the school's functional requirements. This design is projected to significantly accelerate the attendance reporting process compared to conventional methods.